2018
DOI: 10.1088/1361-6463/aabc04
|View full text |Cite
|
Sign up to set email alerts
|

A parametric model for the changes in the complex valued conductivity of a lung during tidal breathing

Abstract: A parametric model for the changes in the complex valued conductivity of a lung during tidal breathing. Journal of Physics D: Applied Physics, 51 (20) .

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 30 publications
(84 reference statements)
0
7
0
Order By: Relevance
“…The improvements achieved by implementing multifrequencies has been demonstrated on different phantoms [26] and in human subjects [27]. It has been shown that even the permittivity changes become significant at certain frequencies [28].…”
Section: ∇ ( ( )∇ ( )) =mentioning
confidence: 99%
See 1 more Smart Citation
“…The improvements achieved by implementing multifrequencies has been demonstrated on different phantoms [26] and in human subjects [27]. It has been shown that even the permittivity changes become significant at certain frequencies [28].…”
Section: ∇ ( ( )∇ ( )) =mentioning
confidence: 99%
“…Due to this constraint the validation of the proposed approach was restricted to single frequency mode (200 kHz). Considering the frequency used is below the MHz band, based on simulations done in [28], the real parts of the measurements were used to demonstrate that the proposed approach is effective even with the aforementioned hardware limitations. After the estimated conductivity distribution is computed, the next step involves finding which of the pre-defined models in the model library could best describe the achieved solution.…”
Section: ∇ ( ( )∇ ( )) =mentioning
confidence: 99%
“…In this work, we aim to reconstruct a crack in an area sensor painted atop a reinforced concrete beam element. For this, we utilize ERT, which is a diffusive imaging modality where we aim to reconstruct the electrical conductivity σ from electric potential measurements V [44,45]. The resulting observation model for this problem is written as…”
Section: Damage Invisibility In Ertmentioning
confidence: 99%
“…It is emphasised that this approach is non-parametric in the sense that no statistical assumptions have been made on the population distributions from which the data are drawn. To this end, the non-parametric gold standard constitutes a generic approach which is currently under development and is expected to be useful in many other EIT related issues and investigations where breath delineation and tidal breathing is of great importance, see e.g., [26].…”
Section: Accepted Manuscriptmentioning
confidence: 99%